Brethern or Strangers?: Samaritans in the Eyes of Second-Century B.C.E. Jews - Bourgel, Jonathan (Biblica, 2017)
The process leading to the ultimate estrangement between Jews and Samaritans is commonly regarded as having occurred in the second century B.C.E. This paper aims at giving an outline of how the Samaritans of that time were conceived by the Jews and to determine whether the latter were already perceived as a well-defined alien group. The picture that emerges from the Jewish sources is remarkable in that not only were there divergent opinions among the Jews in regard to the Samaritans, but also that the borders between the two communities were still blurred and even in parts overlapped each other.